# Growing Squares

Extracts from this document...

Introduction

John McLaughlin – john_mclaughlin@email.com

Feel free to e-mail me on ways to improve this essay it would be a great help.

## Growing Squares

I have decided to find a formula to find the nth term. To help me find the nth term I shall compose a table including all the results I know.

## Pattern Number | ## Number of Squares | ## 1st Difference | ## 2nd Difference | |

1 | 1 | 4 | 4 | |

2 | 5 | |||

8 | ||||

3 | 13 | 4 | ||

12 | ||||

4 | 25 |

The 2nd difference is constant; therefore the equations will be quadratic. The general formula for a quadratic equation is an2 + bn +c. The coefficient of n2 is half that of the second difference

Therefore so far my formula is:2n2 + [extra bit]

I will now attempt to find the extra bit for this formula.

## Pattern Number | ## Extra Bit | ## 1st Difference | ## 2nd Difference | ||||

1 | 2 | 6 | 4 | ||||

2 | 8 | ||||||

10 | |||||||

3 | 18 | 4 | |||||

14 | |||||||

4 | 32 |

From my table of results I have found the formula to be 2n2 + 2n + 1

I will now check my formula by substituting a value from the table in to my formula:

E.g. n = 2

Un = 2 (2) 2 – 2 (2) + 1 = 8.

For Diagrams 1 – 4 I can see a pattern with square numbers.

Middle

Therefore so far my formula is:3n2 + [extra bit]

I will now attempt to find the extra bit for this formula.

## Pattern Number | ## Extra Bit | ## 1st Difference | ## 2nd Difference | |

1 | 0 | 6 | 6 | |

2 | 6 | |||

12 | ||||

3 | 18 | 6 | ||

18 | ||||

4 | 36 |

From my table of results I have found the formula to be3n2 + 3n + 1

I will now check my formula by substituting a value from the table in to my formula:

E.g. n=3

Un=3(3) 2 -3(3) + 1 = 19.

For my table of results I can see that my formula is correct after verification.

I have chosen to justify my formula using 3 simultaneous equations rather that geometrically like the previous investigation.

The standard quadratic formula » U = an2 + bn + c

I will now substitute values for U and n

7 = a (2) 2 + 2b + c (1)

19 = a (3) 2 + 3b + c (2)

37 = a (4) 2 + 4b + c (3)

If we then subtract equation (2) from (1) we get

12 = 5a +b (4)

When we do the same between (3) and (2)

18 = 7a + b (5)

(5) – (4) = 6 = 2a

Therefore a = 3

To work out b we must insert the value of a in to equation (4)

(4) » 12 = 5 (3)

Conclusion

Therefore so far my formula is:4/3n2 - 2n² [extra bit]

## Pattern Number | ## Extra Bit | ## 1st Difference | ## 2nd Difference | |

1 | 12/3 | |||

2 | 41/3 | |||

3 | 7 | |||

4 | 91/3 | |||

5 | 121/3 | |||

Therefore my formula is:

4/3n³ – 2n² + 8/6n – 1

I will test this formula out on a pattern previously drawn out and recorded.

Un = 4/3n³ – 2n² + 8/6n – 1

36 – 18 + 4 – 1

= 25

This is correct

I will now and justify the formula by using simultaneous equations.

Let C= An³ - bn² +cn – d

When n = 1, c = 1. Therefore:

1= a +b + c + d (1)

When n = 2, c = 7. Therefore:

7 = 8a + 4b + 2c + d (2)

When n = 3, c = 25. Therefore:

25 = 27a +9b + 3c + d (3)

When n = 4, c = 65. Therefore:

63 = 64a + 16b + 4c + d (4)

If we then subtract equation (2) from equation (1) we get

6 = 7a + 3b + c (5)

If we do the same again to (3) and (2), we get

18 = 19a + 5b + c (6)

Then to (4) and (3)

38 = 37a + 7b + c (7)

Then to (6) and (5)

12 = 12a + 2b (8)

Then again to (7) – (6)

20 = 18a + 2b (9)

And finally to (9) and (8)

A = 8/6 = 4/3

Substitute into 8

12 = 16 + 2b

-2 = b

Substitute into 5

6 = 9 1/3 – 6 + c

2 2/3 = c = 8/3

Substitute into 1

1 = 4/3 + (-2) + 8/3 + d

-1 = d

Therefore my formula is as follows;

C=4/3n³ – 2n² + 8/6n – 1

This is correct.

John McLaughlin – john_mclaughlin@email.com

Feel free to e-mail me on ways to improve this essay it would be a great help.

This student written piece of work is one of many that can be found in our AS and A Level Core & Pure Mathematics section.

## Found what you're looking for?

- Start learning 29% faster today
- 150,000+ documents available
- Just £6.99 a month